Morphological characterization of fruits, endocarp, seed and seedlings of cajá-manga (Spondias dulcis) - Magalhães de Souza, Pedro Henrique; Rodrigues Gomes, Francielly; Zildo da Silva, Givanildo; Rocha, Diego Ismael; Silva Cruz, Simério Carlos; Pereira da Silva, Danielle Fabíola (Revista Ceres, 2025)
The Cerrado biome has several species that can generate income, and the cajá-manga is one of these native species with great potential but with scarce information about its morphological characterization. Thus, this work aimed to characterize the fruit, endocarp, seeds, and seedlings of cajá-manga morphologically. The fruits were evaluated by the characteristics of the length, width, and diameter of the fruit, endocarp, and seeds, the number of loculi, and the weight of fruits and endocarp. The plantlets were evaluated for the number of seedlings per endocarp, number of leaflets, number of leaflets of the 3rd and 4th leaves, stem diameter, length of the shoot and root, root and shoot dry matter and data analyzed by descriptive analysis. The morphometric characteristics of the fruits, endocarp, and seeds were analyzed using the Scott-Knott test. The morphological characteristics of the fruits, the endocarps, the seeds, and the plantlets of cajá-manga varied within the mother plants. These results can be used as a basis for future selection of plants with desirable characteristics on breeding programs.